Assessment the Effects of Ciprofloxacin and Gentamicin Alone or in Combination to Induce Hepatic Toxicity in Rats - Jawad Kadhim Faris (Journal of Global Pharma Technology, 2019)
The aim of this study was to research the comparative effects of ciprofloxacin (CP)  and gentamicin (GT) alone or in combination on the deleterious effects on liver function  and histopathological architecture in rats for  (10) days administration. Doses of 100 mg/kg were used for each of  CP and GT ,and each of both drugs 50mg/kg were combined to estimate the synergistic effect .Thirty two  rats were divided into four groups , group I :control , (1 ml/kg saline orally) group 2: CP  (100 mg/kg orally)  for (10) consecutive days , group 3:  GT  (100 mg//kg) intraperitoneally (i/p)  for (10) consecutive days, group 4: CP  (50 mg/kg orally) plus GT  (50 mg//kg)  i/p  for (10) consecutive days . Blood and liver collected for biochemical and histopathological examination of the liver. The degree of liver injury was determined by measuring biochemical markers, the serum activity of Alanine aminotransferase (ALT), Aspartate aminotransferase (AST) and Malondialdehyde (MDA) levels, as measures of oxidative stress. The results of this study showed that in the serum of the rats in the test groups were found to be significantly higher (p < 0.01) than control group; this effect was found to vary among the groups. These findings are indicative that combination of CP + GT more injury to hepatocytes than GT and CP respectively .The synergistic effects of combination of CP + GT showed the higher levels of liver enzyme and sever liver injury.  Keywords:  Gentamicin, Ciprofloxacin, Combination Hepatotoxicity.